Response of chamomile to spraying with heparin solution in growth , yield and oil content - Mustafa, Sala Basim Ismael; Nasserallah, Adil Usif (Journal of Kerbala for Agricultural Sciences, 2018)
The experiment was conducted during the winter farming season 2010 – 2011 in the field of experiments of the Department of Field Crops – College of Agriculture l University of Baghdad to determine the response of Chamomile common (Iraqi) to study spraying effect of Heparin solution at a concentration (0 , 2.5 , 5) ml. L-1 on growth , yield , and volatile oil content an experiment were arranged according to the Randomized Complete Block Design with three replicates using 9 treatments , the experimental results of this experiment showed that : treating plants with H2 caused significant effects on all characters studied : number of total branches (57.60) branches . plant-1 , number of flower branches (45.36) branches. plant-1 ,number of leaves (166.50) leaf. plant-1 , leaf area (76.56) cm2. plant-1 , Chlorophyll content (78.36) mg. g-1. Leaf tissue , the inflorescence stalk length (77.16) cm, the time to the appearance of flower buds (95.76) day , the time to the appearance of flowering (112.43) day , number of inflorescence (169.93) flower. plant-1 , percentage of fruit – set (92.80)% , inflorescence diameter (6.33) cm , The fresh weight of the inflorescence (1758.23) kg.ha-1 , the dry weight of the inflorescence (721.57) kg.ha-1 , flowers oil content (1.50)% , yield of oil (26.50) L. ha-1 , Specific gravity (0.955) , oil density (0.946) mg. microletter, refractive index (1.490) degree. High – performance Liquid Chromatography analysis showed that treating plants with H2 , gave greater values of all 7 volatile compounds fractionated Chamomile oil.